Reformulation of Asset Recovery Strategy Resulting from Corruption Crimes as an Effort to Recover State Losses - Priyana, Puti; Gunawan, Tanumihardja Jopie (Jurnal Cita Hukum, 2024)
It is time for the state to prioritise asset recovery for state losses resulting from criminal acts of corruption. Asset recovery must be an integral part of the series of actions taken against criminal acts of corruption. However, the arrangements for recovering criminal assets in Indonesia are not yet synergistic and overlapping. The asset recovery process is carried out by several agencies, giving rise to sectoral egos and lengthy coordination. This results in the recovery of criminal assets in Indonesia as an effort to recover losses from criminal acts is not optimal. This research recommends strategies for recovering criminal assets in Indonesia to produce efficient asset recovery. The research method used is normative juridical using a statutory approach, comparative analysis, concept analysis and case analysis. The research results found that the suboptimal asset recovery in Indonesia was caused by disharmony in the asset recovery arrangements. Indonesia can reflect on the criminal asset recovery mechanisms in the United States, United Kingdom, and Italy regarding harmonising asset recovery arrangements. This research also found that harmonising asset recovery arrangements in Indonesia should be accommodated through the amendment of KUHAP. Through the harmonisation of these arrangements, The Attorney General's Office of Indonesia, a law enforcement agency that has the authority to carry out investigations, prosecutions, and execution of court decisions that have a permanent legal force appointed as the coordinator of asset recovery for criminal acts so that the recovery of assets, especially those resulting from criminal acts of corruption, can be well synergised and state losses recovery to be optimal.